The Implication of Cyberspace Towards State Geopolitics - Iqbal Ramadhan (Politicon : Jurnal Ilmu Politik, 2021)
Massive technological advancements have influenced many dynamics of the nation's social, political, and economic changes. Geopolitical studies, as one of the studies that investigate the interaction between political dynamics and geography, are exposed to the implications of these technological developments. At the outset of its development, geopolitical studies discussed the state's strategies and policies for gaining influence in specific areas. Geopolitics is the study of a country's boundaries. The emergence of cyberspace, along with the advancement of technology, has implications for a country's geopolitical development. Geopolitical competition takes place not only in the physical realm, but also in cyberspace. The purpose of this article is to examine the shift in the geopolitical paradigm from physical to cyberspace. The authors examine how the existence of cyberspace can have a political impact, particularly geopolitical rivalries between countries, using geopolitics and cyberspace concepts. This scientific article investigates cyberspace phenomena and geopolitical studies using qualitative methods, particularly case study writing techniques. The author contends that geopolitics in cyberspace has no borders, based on the findings of this article's analysis. To avoid cyber conflicts, states must make cyberspace their political domain. Geopolitical rivalries between states in cyberspace can have real-world consequences. One of them is the use of technology to suppress other states' geopolitical policies. Because cyberspace is infinite, the state must develop governance so that the potential for cyber conflicts does not have physical consequences for the country's geopolitics. Given that almost all dynamics of state life have been integrated into information technology, the author concludes that cyberspace should be considered one of a state's geopolitical areas.